Artificial Intelligence: A Glance on Voice Recognition Techniques (Trinity Journal of Management, IT & Media (TJMITM), 2022)
Artificial intelligence is the study of intelligent behaviour. “It is the science where  we build intelligent machines”-Wagner. By this he meant that the main aim is to  programme these intelligent machines like computers to analyse and understand  the human behaviour. Many people thought that intelligence of the human can be  grasped by writing several programs and some other researchers thought that many  fundamentals should be needed to achieve the desired task. Using the computer,  we can execute or simulate any kind of the work we do. So computers are the right  machines where the artificial intelligence can be developed. Some researchers  developed other computing machines expecting that they will perform better than  the computer in many other ways. Many billions of dollars spent on inventing the  new machines that were faster than the computer simulating the programmes. But  the computers must be very fast as much as the programme. While you are going  to know about artificial intelligence, questions like What is intelligence? How can  u measure intelligent? Become pretty meaningful. Here the intelligent agent is  the programme itself which analyse its environment. Human minds and modern  digital computers are similar to each other like symbolic information processing  systems. Both take the symbolic information as the input, manipulate it according  to some set of rules and then they will solve the problems. Artificial intelligent  researchers set some algorithms to identify the intelligent human behaviour so  that they can reproduce the same behaviour automatically. This behaviour can be  observed from the human behaviour in the medical diagnosis, chess, any game  playing, language processing etc. An important feature of AI is Voice Recognition.  Voice recognition is a technology used to recognize a particular voice. Voice signals  form the basis for the speaker identification. We can use voice targeting in many  application areas such as phone banking, phone shopping, database access and  voice mail. One of the most powerful applications of voice recognition for security  is where One can enter their voice for verification. Speech is the basic form of  communication between people.  Speech recognition is the process of converting
Keywords: Artificial Intelligence; intelligent; speech recognition; modelling; speech processing